Construction and Development of a Cardiac Tissue-Specific and Hypoxia-Inducible Expression Vector - Shahrooz Ghaderi; Neda Alidadiani; Jafar Soleimani Rad; Hamid Reza Heidari; Nafi Dilaver; Behzad Mansoori; Reza Rhabarghazi; Rezayat Parvizi; Vahid Khaze Shahgoli; Behzad Baradaran (Tabriz University of Medical Sciences, 2018)
Purpose: Cardiovascular gene therapy is a sophisticated approach, thanks to the safety of vectors, stable transgene expression, delivery method, and different layers of the heart. To date, numerous expression vectors have been introduced in biotechnology and biopharmacy industries in relation to genetic manipulation. Despite the rapid growth of these modalities, they must be intelligently designed, addressing the cardiac-specific transgene expression and less side effects. Herein, we conducted a pilot project aiming to design a cardiac-specific hypoxia-inducible expression cassette. Methods: We explored a new approach to design an expression cassette containing cardiac specific enhancer, hypoxia response elements (HRE), cardiac specific promoter, internal ribosome entry site (IRES), and beta globin poly A sequence to elicit specific and inducible expression of the gene of interest. Enhanced green fluorescent protein (eGFP) was sub-cloned by BglII and NotI into the cassette. The specificity and inducible expression of the cassette was determined in both mouse myoblast C2C12 and mammary glandular tumor 4T1 as 'twin' cells. eGFP expression was evaluated by immunofluorescence microscope and flow cytometry at 520 nm emission peak. Results: Our data revealed that the designed expression cassette provided tissue specific and hypoxia inducible (O2<1%) transgene expression. Conclusion: It is suggested that cardiac-specific enhancer combined with cardiac-specific promoter are efficient for myoblast specific gene expression. As well, this is for the first time that HRE are derived from three well known hypoxia-regulated promoters. Therefore, there is no longer need to overlap PCR process for one repeated sequence just in one promoter.